Contact metamorphism in pelitic rocks on the island of Kos (Greece, Eastern Aegean sea): a test for the Na-in-cordierite thermometer - Kalt, Angelika; Altherr, Rainer; Ludwig, Thomas (Journal of petrology, 1998)
Most of the applicable thermometers involving cordierite require additional Fe-Mg phases and knowledge of pressure and fluid phase composition. These conditions are not necessarily met with natural cordierite-bearing metamorphic rocks. A potential pressure-independent geothermometer for cordierite- and plagioclase-bearing rocks is the experimentally determined inverse linear relationship between temperature and Na contents of Mg-cordierite coexisting with NaOH or albite and NaOH. In this paper, the Na-in-cordierite thermometer is empirically tested on cordierite-bearing metapelites from the island of Kos, contact metamorphosed by a quartz monzonite intrusion. The variety of phase assemblages in the metapelites allows for tight constraints to be placed on temperatures (508-762°C) and pressure (0.2 GPa) during contact metamorphism by calculated and experimentally determined phase equilibria and by Al-in-hornblende barometry. Fluid compositions are crudely estimated from the presence and absence of graphite and calcite and from 2Vx in cordierite. Applying the Na-in-cordierite thermometer to 19 rock samples taken at increasing distances from the intrusion yields realistic peak temperatures. The Na-in-cordierite temperatures are consistent with constraints from petrogenetic grids, with experimentally determined phase equilibria and with temperatures based on Fe-Mg exchange equilibria (garnet-cordierite and garnet-biotite), although the latter tend to give lower temperatures. The Na-in-cordierite temperatures show no systematic variations with Mg values and Al contents of cordierites, Na contents of coexisting plagioclase (in the range An10-An40) and biotite, and H2O/CO2 ratios in coexisting fluids, though the last are only poorly known. Cordierites have either high Na and significant Li contents or display low levels of both elements. Li is probably introduced into cordierite by a coupled substitution involving tetrahedral and octahedral sites, whereas Na may not be charge-balanced by lattice oxygen. The results obtained suggest that the experimentally established relationship between Na contents of cordierite and temperature is a useful thermometer for cordierite- and plagioclase-bearing metapelitic rocks. The nature of Na incorporation in cordierite and its relation to fluid composition, however, must be constrained by further experiments.
Gesehen am 20.10.2022